Leading through turbulence [ how a values-based culture can build profits and make the world a better place - Lewis, Alan; Lewis, Harriet (McGraw-Hill, 2012)
Suitable for executives, managers, business owners, or entrepreneurs, this title shows you how to adapt and thrive in times of change and crisis, create a corporate culture that promotes talent and growth, invest in leadership at all levels and in people with potential, and, gives back to the world through good works and philanthropy